ANALISIS KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN KUDUS - Akbar, Meka Fadlalul; Mustam, Moch (Journal of Public Policy and Management Review, 2016)
Transport is an organization of the mobility of people, goods and services having a very important value in order to achieve the transport objectives in an area particularly and the national objectives generally, one of the means of transport is motor vehicle. This study aims to determine the service quality at the Communication and Information Department Kudus Regency based on the theory of Morgan dan Murgatroyd dan Zeithaml et al. The purpose of this study is to analyze the testing services from Tangible, Reliability, Responsiveness, Assurance, Emphathy aspects and services inhibiting factors. The study is conducted using quantitative descriptive method, by taking a total of 100 respondents who are public users of motor vehicles testing services. Based on the results, the motor vehicle testing services quality carried out in the Communication and Information Department Kudus Regency can be considered satisfactory for most service performance levels is above the average of the minimum service performance levels, however, there are services inhibiting factors in the Leadership Behavior, Organizational Communication, Work Motivation, and Social Control. Thus, it is suggested to immediately improve and evaluate the low quality of the performance deals with the reasonable price by reorganizing the high price and the fixed price by giving the bills or the expense details as well as improving the services inhibiting factor. Therefore, the Communication and Information Department Kudus Regency can hopefully improve the service quality better in the future.